DYNAMIC CHARACTERISTICS ANALYSIS OF KEY PARTS（ STEEL WIRE ROPES） OF MOBILE ROLLER CARRIER CONVEYOR BASED ON ADAMS - ZHANG DongSheng; ZHANG Meng; NI Xue (Jixie qiangdu)
In this paper a new mobile wheel bracket conveyor structure as the research object,through theoretical analysis of mobile wheel bracket conveyor running,put forward the connection and pull role-key components of the wire rope running stable and safety requirements. On the basis of the virtual prototype model established by ADAMS,the macro model of ADAMS/View is used to model the wire rope micro model of the connecting roller bracket. Through the dynamic simulation of the conveyor’s motion system,the mobile roller bracket and the wire rope are fully run for one week. In this process,the dynamic characteristics of three adjacent sections of the wire rope at the commutator wheel are analyzed,and the speed of the wire rope position and the change curve of the displacement are obtained,and the mechanical characteristic curves of the shaft sleeve force between the wire rope,the wire rope and the bracket,the contact force of the wire rope and the reversing wheel are obtained. The results show that the movement trend of the wire rope is the same because of the effect of pre-tightening device,but there is a small deviation. And because of the vibration of the flexible body of the wire rope,the speed change of the Y axis and the Z axis in the stable transportation section is produced. In the transfer direction of the conveyor,the effect of the wire rope and the reversing wheel has a certain impact,resulting in a great change in the joint force of the wire rope and the sleeve force of the shaft,the bracket and the wire rope. Therefore,some measures should be taken to prevent the breaking of the wire rope at the transfer direction of the conveyor..